(untitled) (Medical Forum Monthly, 2023)
Objective: To determine the ureteroscopy outcome with holmium laser for renal pelvis stone clearance. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Urology Clinic of Shalamar Hospital Lahore from July 2022 to July 2023. Materials and Methods: 178 patients with renal pelvis stone were included in study. Prior to surgery all patients underwent a CT Scan KUB without contrast for assessment of stone size and location. All procedures were performed using rigid ureter scopes. Outcome were observed in terms of stone free status. IBM SPSS Statistics v27 was used for statistical analysis. Results: Among 178 patients, 75.8% were males. The average patient age and stone size was 34.98±13.95 years and 20.31±4.50 mm. In our study, the first session's stone-free rate was 71.9% and the stone-free rate after the second session was 80%. We found significant mean difference of stone size with regard to stone-free status after the first session. We discovered a significant association of stone size with stone free status after the first session but not for gender and age group. We found significant mean difference of stone size with regard to stone-free status after the second session. We discovered no association for age, gender with stone free status after the second session. Conclusion: Ureteroscopy with holmium laser is an efficient treatment for renal pelvis stones. It also found efficient for male, females, patient with age≤30 years and for patient with age above 30 years.